2014
DOI: 10.1053/j.gastro.2014.09.024
|View full text |Cite
|
Sign up to set email alerts
|

HCV NS5A Inhibitors Disrupt Replication Factory Formation: A Novel Mechanism of Antiviral Action

Abstract: After the embargo period via non-commercial hosting platforms such as their institutional repository  via commercial sites with which Elsevier has an agreement In all cases accepted manuscripts should: link to the formal publication via its DOI  bear a CC-BY-NC-ND license -this is easy to do, click here to find out how  if aggregated with other manuscripts, for example in a repository or other site, be shared in alignment with our hosting policy  not be added to or enhanced in any way to appear more like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…An additional report of direct binding to NS5A protein of DCV and the related compound ledipasvir also supports the direct association of NS5A RCIs with the NS5A protein (8). Immunomicroscopy analysis indicates that DCV binding results in the apparent disassociation of NS5A from the replication complex, consistent with other evidence that NS5A RCI binding has multiple effects (9)(10)(11)(12)(13).…”
supporting
confidence: 77%
“…An additional report of direct binding to NS5A protein of DCV and the related compound ledipasvir also supports the direct association of NS5A RCIs with the NS5A protein (8). Immunomicroscopy analysis indicates that DCV binding results in the apparent disassociation of NS5A from the replication complex, consistent with other evidence that NS5A RCI binding has multiple effects (9)(10)(11)(12)(13).…”
supporting
confidence: 77%
“…DMVs serve as membranous compartment where HCV replication occurs efficiently and safely, protected from cellular RNA sensors and degradation factors [57][58][59]. Interestingly, the Bartenschlager lab and others provided evidence that NS5Ai, like CypI, also prevent the formation of DMVs [55,[60][61]. Importantly, we showed that excepted CypI and NS5Ai, no other classes of anti-HCV agents inhibit the formation of DMVs by HCV [55].…”
Section: Discussionmentioning
confidence: 56%
“…The NS5A phosphoprotein has no known enzymatic activity and its detailed function remains unclear [19]. NS5A inhibitors are thought to interact with NS5A and block formation of the "membranous web" that houses HCV RNA replication.…”
Section: Ns5a Inhibitorsmentioning
confidence: 99%
“…NS5A inhibitors are thought to interact with NS5A and block formation of the "membranous web" that houses HCV RNA replication. They interfere with several functions of NS5A in the HCV life cycle, and disrupt the establishment of replication sites, which in turn prevents continued HVC RNA replication [19]. NS5A inhibitors include daclatasvir, ombitasvir, ledipasvir, elbasvir, and velpatasvir.…”
Section: Ns5a Inhibitorsmentioning
confidence: 99%